"Can we not do group stuff?" : Student insights on implementing co-creation in online intensive programs. - Newell, Samantha J.; van Antwerpen, Natasha (Journal of University Teaching & Learning Practice v.21 n.2 https://doi.org/10.53761/1.21.2.05, 2024)
The demand for intensive educational experiences is increasing, necessitating a focus on ensuring quality and providing adequate student support. Increasing opportunities for student collaboration, including teacher/student co-creation of learning materials, has strong potential to increase engagement and support. Given increased interest in co-creation within education and research more broadly, we explored student perspectives on this novel approach within online intensive modes of teaching with a focus on feasibility and implementation. Two focus groups were conducted with students (N = 16), including discussion of their preferences and barriers for implementing co-creation initiatives in an intensive program. Thematic analysis was then conducted, generating five themes. Students see co-creation as beneficial for self-development and connections (Theme 1), but also identify barriers such as its perception as another group assignment (Theme 2). Students believe successful co-creation requires a "type" of student who is intrinsically motivated and career-driven (Theme 3). Concerns exist about co-creation being an additional workload, emphasising the need for clear roles (Theme 4). Students' views on co-creation vary, with differing opinions on its practicality (Theme 5). The findings suggest that successful implementation of co-creation initiatives requires careful consideration of barriers while addressing student concerns and leveraging their intrinsic motivation. For educators in intensive programs, it is crucial to provide incentives, collaborate on feasible time slots, establish clear objectives and timelines, offer guidance and support, and celebrate student achievements to effectively incorporate co-creation activities. By understanding students' perceptions and preferences, educators can better support student collaboration, which is crucial for students' development in intensive programs. [Author abstract]